TOWARD AN INNOVATIVE LEARNING SYSTEM: REVIEWING STRATEGIES AND RESOURCE UTILIZATION TO STRENGTHEN EDUCATIONAL OUTCOMES - Rahmad Mulyadin Tanjung; Muhammad Habib (Adisam Publisher, 2025)
This study aims to examine innovative learning strategies and optimization of educational resources as an effort to strengthen learning outcomes in the modern education system. Using a qualitative approach based on systematic literature studies, this study synthesizes findings from various international journals that discuss pedagogical innovation, digital technology integration, and the use of learning resources. The results of the study show that strategies such as active learning, project-based learning, blended learning, and inquiry-based learning contribute significantly to increasing student engagement and achievement. Digital technology is emerging as a key enabler that enables personalization of learning, wider content access, and data-driven monitoring. However, the implementation of innovative learning systems faces a number of challenges, including the digital divide, limited competencies of educators, lack of policy support, and a school culture that is not ready to accept change. This research confirms the need for a systemic approach that integrates pedagogy, technology, education management, and policy to create innovative learning systems that are adaptive, effective, and sustainable.